EFEKTIVITAS MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA DI SMP SWASTA HKBP PADANGSIDIMPUAN - Apriani Susanti Simanjuntak (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
Abstract This study aims to describe the effectiveness of using TPS learning model on students’ mathematical reasoning ability on the topic of social arithmetic at the seventh grade students of SMP Swasta HKBP Padangsidimpuan. The research was conducted by applying experimental method (one group pretest post test design) with 25 students as the sample and they were taken by using total sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using TPS learning model was 3.33 9good category) and (b) the average of students’ social arithmetic achievement before using TPS learning model was 48.80 (poor category) and after using TPS learning model was 82.40 (very good category). Furthermore, based on inferential statistic by using pair sample ttest (SPSS 17), the result showed significant value was less than 0.05(0.000<0.05). It means TPS learning model was effective used on students’ mathematical reasoning ability on the topic of social arithmetic at the seventh grade students of SMP Swasta HKBP Padangsidimpuan. Keywords: TPS learning model, reasoning ability, social arithmetic